Congestion control mechanisms and the best effort service model. - Gevros, P.
In the last few years there has been considerable research toward extending the Internet architecture to provide quality of service guarantees for the emerging real-time multimedia applications. QoS provision is a rather controversial endeavour. At one end of the spectrum there were proposals for reservations and per-flow state in the routers. These models did not flourish due to the network's heterogeneity the complexity of the mechanisms involved, and scalability problems. At the other end, proposals advocating that an overprovisioned best effort network will solve all the problems are not quite convincing either. The authors believe that more control is clearly needed for protecting best effort service. An important requirement is to prevent congestion collapse, keep congestion levels low, and guarantee fairness. Appropriate control structures in a best effort service network could even be used for introducing differentiation. This could be achieved without sacrificing the best effort nature of the Internet or stressing its architecture beyond its limits and original design principles. We revisit the best effort service model and the problem of congestion while focusing on the importance of cooperative resource sharing to the Internet's success, and review the congestion control principles and mechanisms which facilitate Internet resource sharing
Keywords: FIFO queues; Internet architecture; Internet resource sharing; QoS guarantees; QoS provision; Best effort service model; Best effort service network; Congestion control mechanisms; Cooperative resource sharing; Fairness guarantee; Overprovisioned best effort network; Quality of service guarantees; Queue management; Real-time multimedia applications; Routers; Scalability problems